Does Energy Policy Risk Threaten Energy Sources Diversification? - Mamadiyarov, Zokir; Eshov, Mansur; Otakhonova, Dinora; Utegenova, Sarbinaz; Sabirov, Khamid; Marks, Adam; Bahodirov, Nu’monkhon (International Journal of Energy Economics and Policy, 2025)
Recently, to enhance energy sources diversification is becoming on the main priorities in the world. However, effective diversification of energy sources is affected by risks associated with energy policy. In this context, the study explores the effect of energy policy risk on energy sources diversification of the panel of 64 countries spanning the period from 2000 to 2018, employing Method of Moments Quantile Regression. The findings indicate that energy policy risk negatively influences on energy sources diversification across all the quantiles, 10-90%. Moreover, the impact of Chinese energy investment on energy sources diversification is investigated using Difference-In-Differences method since Chinese energy investment might serve as an additional factor shaping energy policy in the region. The results show that Chinese energy investment also has a negative effect of energy sources diversification. The policymakers should implement effective policies considering those factors in order to achieve productive diversification of energy sources.